Some Aspects of Efficacy and Residues of Maneb and Mancozeb in Selected Vegetables - S.Ramasamy, (1991)
The use of the fungicides, maneb and mancozeb on selected leafy and fruit vegetables was studied with the view to ascertain their efficacy and degradation of their residues on these crops. The phenology of these vegetables and the disease problems encountered were also verified. Most of the test crops were prone to disease infection if not treated with suitable fungicides. Spinach was susceptible to downy mildew infection while spring onion was predisposed to leaf blight and leaf tip dieback. In leaf mustard and garland chrysanthemum, however, no serious disease infection was encountered. Fruit vegetables were susceptible to several serious diseases. Tomato had early blight, late blight, Fusarium wilt and anthracnose. Cucumber was Infected by downy mildew and anthracnose while chilli was prone to anthracnose, Sclerotium wilt and mosaic virus infection. Maneb and mancozeb when used weekly at recommended rates of 0.27% a.i and 0.2% a.i. respectively were reasonably effective against diseases of leafy vegetables. In tomato, recommended rates of these fungicides, applied at 4-day intervals, gave reasonable control of late blight. In tomato, weekly applications were Ineffective for late blight control especially during high disease pressure. However, reasonable control was achieved at 4-day intervals. In cucumber, downy mildew infection was effectively reduced by the application of these fungicides. Similarly, anthracnose infection on chilli fruits was checked with these fungicides applied weekly at recommended rates. Residues of maneb and mancozeb in spinach exceeded the maximum residue limit of 5 ppm at harvest even when last treated 2 weeks before harvest. In leaf mustard and spring onion, a 14 day PHI appeared a prudent recommendation with these fungicides. This was not a serious problem in tomato and cucumber as even after 3 days the amount detected was less than 1 ppm in all the treatments. Hence a 3 day PHI can be recommended for these crops. In chilli, however, 3-day intervals were insufficient as about 10 ppm was still detected. A 14 day PHI appeared more prudent. Other fungicides such as chlorothalonil, propiconazole or metiram could be used in place of maneb and mancozeb before harvest.